Starzec w polityce. Zmienne poglądy Plutarcha z Cheronei - Osek, Ewa (Vox Patrum, 2011)
Plutarch of Chaeronea (ca. 45-122/125) changed his attitude to on old age in the successive stages of his life and literary production. In the period between AD 85 and 95 the middle-aged author inclined to the Stoic theory on old age. According to the Stoic doctrine his Table talks (Symposiacs) show an old age of man as a heatless and moistures state causing the physical and mental degeneracy. In the next phase – the time of working on the Parallel Lives (AD 96-117) Plutarch hesitated between the pessimistic Stoic view and the neo-Stoic conception of the eugeria („the beautiful ageing”), whose embodiment and ideal was Cato the Elder. The ultimate Plutarch’s position is contained in his last work entitled Whether an old man should engage in public affairs. This treatise on old age, being the only such a work extant in Greek language, was written in AD 119/120, when Hadrian appointed over seventy-year-old Plutarch to a governor of Greece. The author argues now that an old statesman is much better than a young one and that a politician doesn’t have to finish his public career because of his old age. The Plutarch’s sources are not Peripatetic, as most of the scholars suppose, but Epicurean and perhaps also Middle Platonic. The thesis of this article is that the philosopher of Chaeronea always oscillated between Stoicism and Epicureanism in his approach to old age.